Sandra Sherman: Fresh from the Past: recipes and revelations from Moll Flanders’ kitchen - Jaine, Tom (Petits Propos Culinaires, 2005)
Sandra Sherman: Fresh from the Past: recipes and revelations from Moll Flanders’ kitchen, with recipes interpreted by Henry and Karen Chotkowski: Taylor Trade Publishing, Lanham, Maryland, 2004: ISBN 158979088X; 387 pp., colour illus., hardback $28.95, £18.95.